Effects of dietary resveratrol supplementation on egg production and egg yolk lipid peroxidation - Şahin, Kazım; Akdemir, F.; Orhan, C.; Tuzcu, M.; Hayirli, A.; Şahin, Nurhan. (Elsevier Science Inc, 2010)
[Abstract Not Available]
Keywords: resveratrol; antioxidant status; Japanese quail